Entendendo os diferentes: influência de fatores contingenciais e dos estilos de aprendizagem no desempenho acadêmico de discentes do curso de Ciências Contábeis - Borges, Iasmini Magnes Turci (2016)
This study investigates under the Contingency Theory and Learning Styles perspectives the influence of internal contingent factors, internal environment, structure, technical system, pedagogical program strategy, faculty strategy, learning style, and neuro-linguistic programming on the academic performance of accounting students who belong to a State-run Higher Education Institution. The research strategy adopted is a survey with data collection by means of a questionnaire. Data analysis of this quantitative study used descriptive statistics and structural equation modeling. The sample consists of 327 students of the undergraduate degree course in accounting from Maringa State University, who are enrolled from the first to fourth year. The results indicate that the professors have influence on academic performance, showing that the higher the degree of requirement from professors in relation to the students, among other factors, the greater will be the dedication of the student, and in contrary cases, there is a decrease in performance. Contingent factors like internal environment, structure, technical and strategic system of the pedagogical program had no influence on academic performance. Of the investigated learning styles, the visual, auditory and reader/writer NLP did not prove to be factors of direct influence on performance. On the other hand, kinesthetic neuro-linguistic programming negatively influences the performance as the educational system predominantly focuses on the visual, auditory and reader/writer styles, so those students who present the kinesthetic style will be in disadvantage in their learning process. Lastly, as the moderating effects of the types of NLP in respect to the internal factor structure, technical system and the pedagogical program strategy, regarding the performance of students, only the listening NLP proved to be moderator in the relationship of faculty strategy and performance, indicating that students who possess a listening NLP nature are more influenced by the strategies of the faculty.